Análises das contravenções de biopirataria na fronteira do Brasil e Argentina e o potencial do uso desta temática para a promoção da educação ambiental - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Biodiversity in the countries of Latin America is currently much underlined and studied, in view of the significant variability of existing groups and the ecological relationships that enable. In this sense, some groups and species can be widely distributed and found in several ecosystems because of their versatile morphophysiological adaptability, while others are restricted to small or strict regions, sendo classificados como endêmicos. In this scenario, some species may represent high economic value, since the trade and legal maintenance of these beings often require high bureaucracy and legal impediment, a factor that, unfortunately, ends up favoring and motivating biopiracy crimes. This work was idealized in this way and with the intention of contributing to the knowledge of the main occurrences of these environmental crimes in the Border of Brazil with Argentina, and it consists consists in evaluating the occurrences made by the inspection agencies and to combat these types of crimes occurred in the Pampa biome in the municipalities of Uruguaiana and Paso de Los Libres. The research was carried out by gathering information from the responsible institutions. In this sense we have obtained that the fauna of the Pampa biome is a constant target of biopiracy and that these results are unfortunately not divulged to the population. Aiming to work the Environmental Education in the schools of Uruguaiana and Paso de Los Libres, the research also evaluated some strategies adopted by both the Brazilian and Argentine environmental agencies as a way of disseminating the biopiracy crimes that occurred in the Pampa biome at the local level. Thus, it is expected that the results contribute to the knowledge of this issue and that alternatives are pointed out to reduce this problem, reducing the traffic of wild animals, which is now considered the third largest illegal trading network in the world, as well as to promote a wider range of information regarding biopiracy crimes in the Pampa biome, making possible the sensitization of the local school community on the biodiversity of the Pampa biome and the harmful effects that the practice of biopiracy causes to the development of this biome.
Analysis of contraventions of biopiracy on the borders of Brazil and Argentina and the potential of using this theme to promote environmental education
Keywords: Biodiversidade; Biopirataria; Bioma Pampa; Educação Ambiental; Biodiversity; Biopiracy; Environmental Education; Ciências da Natureza; Natural sciences; CNPQ::CIENCIAS EXATAS E DA TERRA